The Role of Financial Technology in Improving the Profitability - Mounzer, A. Mourhij (INTI International University, 2025)
This study investigates how FinTech transforms traditional bill discounting—a process characterized by prolonged settlement times, high operational costs, and limited accessibility that constrain business liquidity and profitability. Employing a descriptive-analytical approach with primary data from Syria's unique economic landscape, the research demonstrates that digital bill discounting streamlines trade credit, accelerates settlements, reduces costs, and enhances transactional trust. These operational improvements significantly boost sales, optimize liquidity management, and improve profitability margins across all stakeholders. As a pioneering empirical examination of bill discounting digitalization within the Syrian context, this research provides novel insights for modernizing banking services and fostering sustainable economic growth through targeted financial innovation in challenging environments.